Genetic polymorphisms in patients with celft lip and/or palate non-syndromics - Cárdenas-Nieto, Diana Milena; Leone, Paola E; Paz-y-Miño, César; Forero-Castro, Maribel (Universidad Pedagógica y Tecnológica de Colombia, 2019)
Among the most frequent congenital defects are cleft lip and/or palate (CL/P), with a prevalence of 1:1,000 live births. 70% of CL/P are non-syndromic, which means that they are found as an isolated defect without additional anomalies. They have a complex etiology with both an environmental and genetic component. By the development of human genome sequencing technologies have been identified polymorphic variants that may be associated with the CL/P phenotype and therefore may contribute to the multifactorial etiology of these. This review describes the commonly associated variants and their role in the etiology of CL/P. The SNPs located in the genes IFR6, MSX1, VAX1, PAX9, CHD1, FGF1, GREM1 and WNT3 have been significantly related to the presence of CL/P, and the variants located in the genes APC, GSK3, DVL2, BMP4, ABCA4, BHMT, NTN1, TBX1, EPHA3, FAM49A, MGMT, MMP3, TIMP2 y NOG, although its association with the presence of orofacial fissures has been reported, its relationship with this phenotype is not yet clear. It is important to carry out studies to identify genetic variants that involve specific populations in order to understand the etiology of non-syndromic CL/P.